EVALUASI PENERAPAN SANITASI DI TEMPAT WISATA AGAMA - Putri Tamara; Isra Rizki; Ahmad Deno; Zuli Rodhiyah (Department of Environmental Engineering (Prodi Teknik Lingkungan), Fakultas Sains dan Teknologi, UIN Ar-Raniry Banda Aceh, 2023)
One of the religious tourist destinations available to the public in Jambi City is the Agung Al-Falah Mosque. This mosque is used for worship, this mosque is often utilized for major religious activities. The Grand Mosque of Al-Falah has a rich history. It was constructed in the 18th century by Sultan Thaha Syaifuddin, a leader of the Jambi Sultanate at that time. As a result, this mosque has become one of the significant historical heritages in the city of Jambi. This study aims to examine the implementation of sanitation standards for public places in the Agung Al-Falah Mosque tour in Jambi City. The research employs a mixed-method approach, which combines qualitative and quantitative methods. The assessment is conducted using a checklist and interview instruments, and the collected data are presented. Based on the research findings, it is evident that the assessment of Environmental Aspects (both outside the yard and inside the structure) achieved a percentage of 97.5%, while Sanitation Facilities (Clean Water, Wastewater, Garbage, and Bathrooms) attained a percentage value of 100%. The total score for all sanitation variables used amounted to 98.5%. So, the sanitation implemented in the religious tourism site of the Agung Al-Falah Mosque in Jambi City is deemed healthy, as the total variable score surpasses 75%.